Pengaruh Lingkungan dan Kapasitas Manajerial Terhadap Keputusan Pendanaan Bagi Usaha Kecil Kerajinan 1 di Jawa Timur - Laely, Nur; Komari, Ana (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2017)
This research talks about the environment of craftsmen, Managerial Capacity and Funding Decision for Small Scale Enterprises in East Java. The population of the study was 3,711 craftsmen in East Java. Using Slovin formula with a tolerance of 5%, the sample size was 392 respondents. Test model with Generalized Least Square Estimation (GLS), structural equation model (SEM) analysis, proportional random sampling method and Amos 22 software aid, in 392 respondents. The test results show the model (fit) seen from the value of GFI, AGFI, TLI, CFI, RMSEA and CMIN / DF, each of 0.927, 0.914, 0.965, 0.968, 0.072 and 1.284 are all within the expected range of values so that the model can be accepted. The results showed that: 1). There is a direct influence of the craftsman’s Environment on the managerial capacity of the craftsmen by 0.720. 2). There is a direct influence of the craftsman’s Environment on the craftsman’s financing decision of 0.679. 3). There is a direct influence of the managerial capacity of the craftsmen on the craftsman’s financing decision of 0.324. 4). There is an indirect influence of the craftsman’s Environment on the financing decision of the craftsman through the managerial capacity of 0.233. Major indirect linkage between environmental variables of craftsmen and financing variables of small craft businesses through managerial capacity variables. This indicates that the managerial capacity of small craft business will increase, with the management of the business environment of the good craftsmen in East Java Province. Keywords: Environment, managerial capacity, funding decision, small business craftsmen